Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ans.15327
|View full text |Cite
|
Sign up to set email alerts
|

General Surgeons Australia's 12‐point plan for emergency general surgery

Abstract: In the last decade, emergency general surgery (EGS) in Australia and New Zealand has seen a transition from the traditional on‐call system to the acute surgical unit (ASU) model. The importance and growing demand for EGS has resulted in the implementation of the General Surgeons Australia's 12‐point plan for emergency surgery. Since its release, the 12‐point plan has been used as a benchmark of a well‐functioning ASU, both locally and abroad. This study aims to provide a descriptive review on the relevance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
(173 reference statements)
2
9
0
1
Order By: Relevance
“…The ASU model has been described as a consultant‐led service 3 . This principle aligns with the results of this study, which showed that a greater proportion of consultant cases were performed in the ASU cohort.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The ASU model has been described as a consultant‐led service 3 . This principle aligns with the results of this study, which showed that a greater proportion of consultant cases were performed in the ASU cohort.…”
Section: Discussionsupporting
confidence: 82%
“…Time to the operating room has been described as a key benefit of the ASU model and is commonly implicated in superior patient outcomes 3,6 . The main reason behind reducing time to theatre is to improve overall clinical outcomes and patient care; prompt treatment of emergency cases leads to lower complication rates, lower risk of perforation and shorter hospital admissions 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Therefore, General Surgeons Australia advocates for emergency surgery to be performed during the working day unless there is a threat to life, limb or organ. 20 An ACS model of care can help achieve this goal in theory 21 and, as this study shows in relation to appendicectomy, in practice as well.…”
Section: Discussionmentioning
confidence: 85%
“…However, we found that extensive national and international heterogeneity exists in the structure of ACS models, most likely due to discrepancies in healthcare environment, hospital infrastructure, and available resources [26]. We identified relevant structural components of ACS services using the criteria for ACS models formulated by the AAST Committee for Acute Care Surgery, the GSA 12-point plan (Table 3), and components frequently reported in the ACS literature (Table 2) [3,71]. Previous systematic reviews have focused on clinical and financial outcomes of ACS models [21].…”
Section: Discussionmentioning
confidence: 99%